TPMET: a path to knowledge about mathematics - Martins, Cristina (2014)
From this study it is possible to conclude that teachers’ Aida, Dora and Sara, participation in PFCM has contributed to their professional development, each teacher, however, presenting specific gains in dimensions such as didactic knowledge, teaching practice and reflection upon practice. For instances, regarding their knowledge about Mathematics it is possible to conclude that theachers Aida, Dora e Sara have acquired a new vision about the nature of this subject. Specifically, concerning learning undertaken, important improvements can be remarked about mathematical themes which had not had been part of their initial academic curricula (for instances themes Geometry and Gathering, organizing and analyzing data). In Dora’s specific case a significant improvement in her relationship with mathematics has been noticed. This teacher presented a negative relationship with this subject as a result of a traumatic experience in a Mathematics class, with her primary school teacher, as well as a weak investment in training in this area. It can also be concluded that the contributions achieved are mainly related to: (i) the relationship of the teachers towards mathematics and their taste for learning; (ii) the characteristics of PFCM.